Multi-criteria analysis of green bonds: Hybrid multi-method applications - Lombardi Netto, Antonio [UNESP]; Salomon, Valerio Antonio Pamplona [UNESP]; Ortiz Barrios, Miguel Angel (MDPI, 2021)
There is an increasing pressure by the community and customers forcing companies to insert environmental concerns in their practices. To help companies initiatives, the green bonds market was created. Our research question is “How to select bonds in a growing billion-dollar market?” This paper presents a multi-criteria decision analysis (MCDA) model to enable investors identify opportunities based not only in opinions, but grounded on objective facts. Analytic hierarchy process (AHP), complex proportional assessment (COPRAS), full consistency method (FUCOM), step-wise Weights Assessment Ratio Analysis (SWARA), and technique of order preference similarity to the ideal solution (TOPSIS) are MCDA methods applied in this paper. Top-fifteen green bonds ranked by specialized media were assessed with the proposed MCDA model. Criteria included the Environmental Performance Index (EPI) proposed by Yale University, and common financial indicators as assets, risks (β), and dividends. The new ranks from MCDA are compared each other and compared with the rank published by specialized media.
Keywords: AHP; COPRAS; Corporate finance; Environmental performance; Financial planning; FUCOM; Green bonds; MCDA; SWARA; TOPSIS